Management of diastasis of the rectus abdominis muscles: recommendations for swedish national guidelines. (September 2021) - Carlstedt, Anders; Bringman, Sven; Egberth, Mattias; Emanuelsson, Peter; Olsson, Anders; Petersson, Ulf; Pålstedt, Joakim; Sandblom, Gabriel; Sjödahl, Rune; Stark, Birgit; Strigård, Karin; Tall, Jael; et al.
Background: Diastasis of the rectus abdominis muscle is a common condition. There are no generally accepted criteria for diagnosis or treatment of diastasis of the rectus abdominis muscle, which causes uncertainty for the patient and healthcare providers alike. Methods: The consensus document was created by a group of Swedish surgeons and based on a structured literature review and practical experience. Results: The proposed criteria for diagnosis and treatment of diastasis of the rectus abdominis muscle are as follows: (1) Diastasis diagnosed at clinical examination using a caliper or ruler for measurement. Diagnostic imaging by ultrasound or other imaging modality, should be performed when concurrent umbilical or epigastric hernia or other cause of the patient's symptoms cannot be excluded. (2) Physiotherapy is the firsthand treatment for diastasis of the rectus abdominis muscle. Surgery should only be considered in diastasis of the rectus abdominis muscle patients with functional impairment, and not until the patient has undergone a standardized 6-month abdominal core training program. (3) The largest width of the diastasis should be at least 5 cm before surgical treatment is considered. In case of pronounced abdominal bulging or concomitant ventral hernia, surgery may be considered in patients with a smaller diastasis. (4) When surgery is undertaken, at least 2 years should have elapsed since last childbirth and future pregnancy should not be planned. (5) Plication of the linea alba is the firsthand surgical technique. Other techniques may be used but have not been found superior. Discussion: The level of evidence behind these statements varies, but they are intended to lay down a standard strategy for treatment of diastasis of the rectus abdominis muscle and to enable uniformity of management.